The eccentric short-period orbit of the supergiant fast X-ray transient HD 74194 (=LM Vel) - Gamen, Roberto Claudio (2015)
Aims. We present the first orbital solution for the O-type supergiantstar HD 74194, which is the optical counterpart of the supergiant fastX-ray transient IGR J08408-4503. Methods. We measured the radialvelocities in the optical spectrum of HD 74194, and we determined theorbital solution for the first time. We also analysed the complexHα profle. Results. HD 74194 is a binary system composed of anO-type supergiant and a compact object in a short-period (P=9.5436± 0.0002 d) and high-eccentricity (e=0.63 ± 0.03) orbit.The equivalent width of the Hα line is not modulated entirely withthe orbital period, but seems to vary in a superorbital period (P=285± 10 d) nearly 30 times longer than the orbital one.